Allocation of national renewable expansion and sectoral demand reduction targets to municipal level - Schneider, Simon; Paráda, Edit; Sengl, David; Baptista, José; Oliveira, Paulo Moura (Frontiers in Sustainable Cities, 2024)
Despite the ubiquitous term "climate neutral cities", there is a distinct lack of quantifiable and meaningful municipal decarbonization goals in terms of the targeted energy balance and composition that collectively connect to national scenarios. In this paper we present a simple but useful allocation approach to derive municipal targets for energy demand reduction and renewable expansion based on national energy transition strategies in combination with local potential estimators. The allocation uses local and regional potential estimates for demand reduction and the expansion of renewables and differentiates resulting municipal needs of action accordingly. The resulting targets are visualized and opened as a decision support system (DSS) on a web-platform to facilitate the discussion on effort sharing and potential realization in the decarbonization of society. With the proposed framework, different national scenarios, and their implications for municipal needs for action can be compared and their implications made explicit. This is a provisional file, not the final typeset article.balanced. But there is little to no framework to ensure this (Leal and Azevedo, 2016); Most research is focused on climate neutral citiesits carbon accounting is considering the interplay with the surrounding energy system predominantly in terms of individual offsetting credits, which are known to require further work (Huovila et al., 2022) and are often found to be insufficient (Reckien et al., 2018;Salvia et al., 2021).Much research is focused on evaluating different municipal plans and on developing and applying methods to benchmark incremental progress rather than normative targets (Zhang et al., 2023). In fact, carbon accounting of municipalities varies widely in both scope and method, rendering resulting accounting balances mostly incompatible. Carbon accounting per capita e.g., can give a good indication for individuals but does not help municipalities in identifying climate goals that sufficiently contribute to achieving Paris 2050. The same is true for energy balances, where there are virtually no quantifiable municipal targets considering national energy transition scenarios with certain effort sharing and allocation mechanisms, with notable exceptions: (